High-quality genome sequencing and description of Dermabacter indicis sp. nov. (May 2016) - Lo, C.I.; Sankar, S.A.; Ehounoud, C.B.; Mediannikov, O.; Labas, N.; Caputo, A.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF11 T was isolated from the wound on a researcher's finger who had been bitten by a fish ( Protopterus annectens ) in Senegal. Analysis by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry did not provide any identification, but the 16S rRNA sequence exhibited 97.9% identity with Dermabacter hominis. Phenotypic and genomic analyses demonstrated that strain FF11 T is Gram-positive, facultatively anaerobic, nonmotile and non–spore forming; it exhibited a genome of 2 222 902 bp encoding 2074 protein-coding and 50 RNA genes, with a 63.2% G+C content. We consequently proposed the creation of Dermabacter indicis strain FF11 T .